If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y = 2(y + -5) + -5 Reorder the terms: 4y = 2(-5 + y) + -5 4y = (-5 * 2 + y * 2) + -5 4y = (-10 + 2y) + -5 Reorder the terms: 4y = -10 + -5 + 2y Combine like terms: -10 + -5 = -15 4y = -15 + 2y Solving 4y = -15 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4y + -2y = -15 + 2y + -2y Combine like terms: 4y + -2y = 2y 2y = -15 + 2y + -2y Combine like terms: 2y + -2y = 0 2y = -15 + 0 2y = -15 Divide each side by '2'. y = -7.5 Simplifying y = -7.5
| 8b=216 | | 3(4x-3)=5-2x/4 | | 6w+9=18w-3w+81 | | -2V+r=2k | | X-12y=-62 | | 0.5=-0.6ln(x)+1 | | y-49=-2 | | 86-2x=6-10x | | 1/x^3=0 | | 0=x-4+3x | | 1/x^3 | | 2xy+3z+1=0 | | x-3-8x-6= | | 5x-2=13x-19 | | 5w^2-30w+40=0 | | 80-5x+4x+10+80=180 | | -6(4y)= | | 6u+6(u-6)=36 | | 4x+10+80-5x=180 | | 13d^2-7d=0 | | -x+17y=127 | | 4(2x-1)-(-3+7)= | | 2y+9=4y-3 | | -1-7x=36x+6(-7-x) | | 4x^4y-36x^3y+80x^2y= | | (17+a)+12= | | x+3=x+11 | | 3z=6z-1 | | 2(-1-3x)=25+3x | | 4M-2(M+6)=5(3M-2)+6 | | 4+4(4x-4)=8-3(2x+1) | | 2y+2=-3 |